PELAKSANAAN PERSYARATAN TEKNIS DEPOT AIR DALAM UPAYA MEMBERIKAN PERLINDUNGAN KEPADA KONSUMEN DI KOTA PONTIANAK - NIM. A1011201065, FITRIANI (Jurnal Fatwa Hukum, 2024)
Abstract  In order to guarantee the quality of drinking water products produced by refill drinking water depots that meet drinking water quality requirements, it is necessary to have provisions governing the existence of refill drinking water depots in an effort to provide protection to consumers of these water depots. In this research the author uses empirical research methods and is descriptive in nature, the aim of this research is to obtain data and information on water depots, factors that refill water depot entrepreneurs have not implemented the provisions as intended in Article 7 paragraph (2) paragraph (2), legal consequences for entrepreneurs who do not implement the provisions of Article 7 paragraph (2) paragraph (2), as well as the role of the Pontianak City Department of Industry, Trade, Energy and Mineral Resources in supervising or preventing business actors from not implementing Article 7 paragraph (2) Decree of the Minister of Industry and Trade Number 651/Mpp/Kep/10/2004 Concerning Technical Requirements for Drinking Water Depots and Trade. The results of this research show that water depot entrepreneurs in Pontianak City have not carried out their obligations regarding Article 7 paragraph (2) of Decree of the Minister of Industry and Trade Number 651/Mpp/Kep/10/2004 concerning Technical Requirements for Drinking Water Depots and Trade. The factor that causes Water Depot entrepreneurs not to comply with Article 7 paragraph (2) is that they do not understand the regulations, namely in accordance with Article 7 paragraph (2) paragraph (2). The legal consequences for water depot entrepreneurs who do not comply with the provisions of Article 7 paragraph (2) are taking administrative action against water depot entrepreneurs, namely verbal warnings, written warnings, temporary suspension of business activities, and revocation of business permits. The efforts of the Department of Industry, Trade, Energy and Mineral Resources of Pontianak City to supervise or prevent water depot business actors who do not implement Article 7 paragraph (2) are to carry out regular and continuous education and supervision, especially regarding Article 7 paragraph (2) Decree Minister of Industry and Trade Number 651/MPP/Kep/10/2004 concerning Technical Requirements for Drinking Water Depots and Trade, which aims to protect the public from disease or health problems.  Keywords: Stock, Gallons, Depot and Water  Abstrak  Dalam rangka menjamin mutu produk air minum yang dihasilkan oleh depot air minum isi ulang   yang memenuhi persyaratan kualitas air minum, perlu adanya ketentuan yang mengatur keberadaan depot air minum isi ulang dalam upaya memberi perlindungan kepada konsumen depot air tersebut. Dalam Penelitian ini Penulis menggunakan   metode penelitian   empiris dan bersifat deskriptif, tujuan   penelitin ini adalah   untuk memperoleh data dan informasi depot air , faktor pengusaha depot air     isi ulang belum melaksanakan ketentuan sebagaimana yang dimaksud dalam Pasal 7 ayat (2) ayat (2), akibat hukum bagi pengusaha yang tidak melaksanakan ketentuan Pasal 7 ayat (2) ayat (2), serta peran Dinas Perindustrian, Perdagangan, Energi dan   Sumber Daya Mineral   Kota Pontianak dalam   mengawasi atau mencegah terhadap pelaku usaha tidak melaksanakan   Pasal 7 ayat (2)Keputusan Menteri Perindustrian Dan Perdagangan Nomor 651/Mpp/Kep/10/2004 Tentang Persyaratan Teknis Depot Air Minum Dan Perdagangannya. Hasil penelitian ini, pihak pengusaha depot air     Di Kota Pontianak belum   melakukan kewajibannya terhadap Pasal 7 ayat (2)Keputusan Menteri Perindustrian Dan Perdagangan Nomor 651/Mpp/Kep/10/2004 Tentang Persyaratan Teknis Depot Air Minum Dan Perdagangannya. Faktor yang   penyebab pengusaha   Depot Air tidak sesuai dengan Pasal 7 ayat (2)adalah adalah belum memahami terhadap peraturan yaitu sesuai dengan Pasal 7 ayat (2) ayat (2). Akibat Hukum Bagi Pengusaha Depot Air yang tidak sesuai dengan Ketentuan Pasal 7 ayat (2) adalah melakukan tindakan administratif   bagi pengusaha depot air   yaitu Teguran lisan, Teguran tertulis, Penghentian   sementara   kegiatan   usaha, dan Pencabutan   izin usaha. Upaya Dinas Perindustrian, Perdagangan, Energi dan   Sumber Daya Mineral   Kota Pontianak   dalam   mengawasi atau mencegah terhadap pelaku usaha depot air yang tidak melaksanakan   Pasal 7 ayat (2) adalah   melakukan edukasi dan pengawasan secara berkala dan berkesinambungan, khususnya terhadap Pasal 7 ayat (2)Keputusan Menteri Perindustrian dan Perdagangan Nomor 651/MPP/Kep/10/2004 tentang Persyaratan Teknis Depot Air Minum Dan Perdagangannya, yang bertujuan untuk melindungi masyarakat dari penyakit atau gangguan kesehatan.Kata Kunci : Stok,   Galon, Depot   dan Air